PELATIHAN PENGELOLAAN POSYANDU DISABILITAS UNTUK OPTIMALISASI LAYANAN INKLUSIF DI POSYANDU SATU HATI KLATEN - Handayani, Sri; Tri Purnomo, Romadhani; Afy Shovmayanti, Noor (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2024)
Integrated  Service Pos (Posyandu) is one of the most important health programs. Currently, posyandu has a broader scope, including services for the elderly and people with disabilities. People with disabilities often still face barriers in accessinghealth services provided by posyandu. These barriers occur due to the lack of knowledge and skills of posyanducadres in providing inclusive services for people with disabilities. For this reason, it is necessary to carry outtraining on the management of posyandu with disabilities for posyandu cadres. The purpose of this activity is to improve the understanding and skills of cadres in managing posyandu with disabilities. The training methods used in this activity were lectures, discussions, questions and answers and demonstrations. The results of the training showed an increased understanding of disability posyandu. The conclusion is that there was an increase in the knowledge of posyandu cadres about the management of disability posyandu